A comparison of reaction diffusion and mechanochemical models for limb development - Maini, P (Plenum Press, 1991)
Several theoretical models have been proposed to attempt to elucidate the underlying mechanisms involved in the spatial patterning of skeletal elements in the limb. Here, I briefly compare two such models - reaction diffusion (RD) and mechanochemical (MC) - and highlight their properties and predictions.